Triple‐Stimuli Responsive Soft Robots with Photo‐Programmable Ferriferous Oxide Particle Patterns - Siwei Hu; Kexing Li; Weijia Nong; Zhong‐Wen Liu; Zhao‐Tie Liu; Yanhu Zhan; Jinqiang Jiang; Peng Yang; Guo Li (Advanced Science)
Abstract Magneto‐driven soft robots featuring remote and highly permeable controllability are considered promising, especially in biomedical and engineering applications. However, there is still lack of a high‐precision method to regulate the distribution of magnetic fillers in polymer substrates, which severely limits the improvement of the actuating functionality. This work provides a photo‐regulatable method to develop soft robots with locally distributed magnetic Fe3O4 nanoparticles. Solvent‐casted polyvinyl alcohol/sodium carboxymethyl cellulose film is prepared as the substrate, and Fe3+ ions are introduced to coordinate with carboxylate groups by surface treatment. Two processes, photo‐reduction of Fe3+ to Fe2+ ions and the hydrolytic reaction of the two ions, are sequentially combined to in situ generate magnetic Fe3O4 particles. Spatiotemporal control of UV light irradiation determines the Fe3+/Fe2+ ratio and, therefore the amount of generated Fe3O4 nanoparticles that decide magnetic field, NIR light, and moisture responsive actuating functionalities. Moreover, the external geometry of the composite can be tuned by inducing the formation of Al3+‐carboxylate coordinates for strain retention, which enables shape programming of the composite to exhibit complex 3D–3D actuating behaviors. The proposed method enables the design and preparation of soft robots with spatially tunable magnetism and more advanced actuating behaviors.